Application of the Cloude-Pottier decomposition to weather radar signatures - M. Galletti; M. Chandra; E. Pottier; A. Ghorbani; A. Ghorbani (Advances in Radio Science, 2005)
In this paper we apply the Cloude-Pottier decomposition to Weather Radar Signatures. First, we present the results of a simulation carried out at the Chemnitz University of Technology and give the expected H-α values for different rain intensities. A comparison with standard radarmeteorological variables is also given. Then, first ever images of Entropy and Anisotropy are presented for clouds and precipitation. Experimental Data are from the POLDIRAD Weather Facility in Oberpfaffenhofen, Germany.